Adios, Hemingway - Padura, Leonardo (Barcelona : Tusquets Editores, 2006)
Mario Conde is a retired Havana cop obsessed with Hemingway, so when the skeletal remains of a man killed on Papa's Cuban estate 40 years earlier are unearthed, it's only natural that the police ask Conde to work the case. As the truth of the night of October 3, 1958, slowly reveals itself, Conde must come to terms with his idealistic memory of Papa Hemingway on Cuba's sun-drenched docks from when he was a child tagging along with his grandfather.
Keywords: Hemingway, Ernest, -- 1899-1961 -- Fiction; Hemingway, Ernest, -- 1899-1961.; Hemingway, Ernest, -- 1899-1961.; Geschichte 2001.; Detective and mystery stories; Authors, American -- Cuba -- Havana -- Fiction; Spanish language materials -- Fiction; Detectives -- Cuba -- Novela; Autores estadounidenses -- Cuba -- La Habana -- Novela; Aufklarung (Kriminologie); Tatverdacht; Verbrechen; Authors, American; Detectives; Cuba; Cuba -- Havana; Kuba -- La Habana; Literatura cubana -- Siglo XXI; Novela -- Siglo XXI; Detective and mystery fiction; Belletristische Darstellung; Mystery fiction; Fiction